Employees' Perception Of Leadership Behaviours - Sheng, Chin Chong (2000)
The research survey was conducted in the state of Melaka involved organizations from all range of industry sector representing both private and public organizations. This survey tests for a relationship between employees' perception of their ratings on individual leader and organization behaviours, and in relation to Total quality Management (TQM).